The Characteristics Of Tourists Doing Culinary Tour: A Case Study Of Lengkong Street Food Bandung - Situmorang, Monica Sehatna; Suryana, Marceilla (Politeknik Negeri Bandung, 2023)
Lengkong Street Food is a culinary tourist attraction that is currently popular in Bandung. This study aims to explain the characteristics of tourists visiting Lengkong Street Food Bandung through socio-demographic, geographic, and psychographic aspects and to find out what types of culinary they like and find out the reasons tourists like these culinary delights. Researchers used a descriptive method in this study with observation, interviews with eleven visitors, and documentation techniques. The results of the research based on the socio-demographic characteristics of tourists are dominated by adolescents and adults with female gender. Based on geographical characteristics, tourists come from outside the city of Bandung. Psychographic characteristics, tourists have interests and expectations. This research found that tourists like culinary types such as Dimsum, BBQ, Suqi, and Steak. The reason tourists like this type of cuisine is because it looks unique, attractive, has affordable prices and has adequate supporting facilities, and offers comfort Keywords: Characteristics of tourists, culinary tourism, Lengkong Street Food Bandung